Design and Operation Characteristics of the Horizontal Swirl Flood Discharge System. Issue 1 (January 2021) - Zhou, Heng; Liu, Jing; Di, Shengjie; Lu, Xi
Abstract: It is one of the effective methods to increase the reliability of flood discharge buildings with high water head and reduce the project cost to transform the diversion tunnel of temporary buildings into permanent spillway by using the horizontal swirl flood discharge system. Based on Gongboxia hydropower station and combined with prototype monitoring, this paper studies and analyzes the key points of shape layout, structural characteristics and operation effect of horizontal swirl flood discharge system, the results show that the horizontal swirl flood discharge system has strong adaptability to topographic and geological conditions, good energy dissipation effect and hydraulic characteristics, stable inlet and outlet flow pattern, stable cyclone cavity, no obvious signs of adverse negative pressure and cavitation erosion, no adverse structural vibration and dynamic response, and safe operation of the spillway tunnel.